EU prepares to launch Economic Partnership Agreement with CARICOM - Tincani, Amos (2004)
Outlines the tenets of the Economic Partnership Agreements (EPAs). Looks at the main advantages for the Caribbean of negotiating an EPA. Mentions the actions that countries from the region must undertake to make the most from an EPA with the European Union.